Age-Period-Cohort analysis and 2036 projections of the burden of ischemic stroke in Finland, Korea, Singapore and China, 1990–2021 - Zhang, Jiayue; Zhao, Bowei; Wang, Kai; Zhao, Lijing; Xu, Zhongxin (Frontiers in Neurology, 2025)
ObjectiveTo analyze the temporal changes in ischemic stroke incidence and prevalence and their correlations with age, period, and birth cohort from 1990 to 2021 in Finland, Korea, Singapore and China, and to predict the trends of incidence and number of cases in 2036.MethodsThe data from the Global Burden of Disease (GBD) 2021 database were used. The effects of age, period and birth cohort on the incidence of ischemic stroke were sorted out by age-period-cohort (APC) modeling. Bayesian Age-Period-Cohort (BAPC) modeling was used to predict the incidence rates of different sex and age groups in 2036.ResultsThe global all-age disability-adjusted life year (DALY) rate of ischemic stroke decreased by 34.90% between 1990 and 2021, with the highest disease burden in China, especially in males. Whereas, Singapore, South Korea, and Finland were lower than the global average. The APC model showed that the incidence increased significantly with the increase of age. Compared with China, the age of high incidence in Singapore, South Korea and Finland has moved forward. In terms of period effect, there were fluctuations across the countries. Although China is less affected by the cyclical effect, the overall burden is increased. In the cohort effect, the incidence of Singapore, Finland, and Korea showed a “U-shape,” while China's prevalence continued to decline. Projections for the next 15 years indicate that the incidence rates in Finland, Korea, and Singapore will remain low, whereas China may continue to increase. By 2036, it could reach nearly 200 per 100,000 people, and the uncertainty is greater, so it needs to focus on prevention and control.ConclusionThe burden of disease for ischemic stroke has been declining in all four countries from 1990 to 2021, but it has been rising in recent years and is expected to continue to rise over the next 15 years.